2004
DOI: 10.1103/physrevb.69.104201
|View full text |Cite
|
Sign up to set email alerts
|

Deuterium atoms and molecules in nanoclusters of molecular deuterium

Abstract: Impurity-helium solids created by injecting deuterium atoms and molecules into superfluid 4 He have been studied via x-ray-diffraction and electron-spin-resonance ͑ESR͒ techniques. X-ray-diffraction measurements show that these solids are highly porous gel-like structures consisting of D 2 clusters with the characteristic cluster size of 90Ϯ30 Å. The densities of D 2 molecules in the samples are 7ϫ10 20 -3ϫ10 21 cm Ϫ3 . Each of the D 2 clusters are either partially or totally surrounded by thin layers of adsor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
38
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 38 publications
2
38
0
Order By: Relevance
“…Clusters grown inside pores obey the growth mechanisms typical of confined geometry and demonstrate the absolute prevalence of structures with the five-fold symmetry [7][8][9]. Such structures were earlier observed in essentially different experiments [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] with the only one common feature, i.e., the limited number of interacting atoms during growth.…”
Section: Introductionmentioning
confidence: 89%
“…Clusters grown inside pores obey the growth mechanisms typical of confined geometry and demonstrate the absolute prevalence of structures with the five-fold symmetry [7][8][9]. Such structures were earlier observed in essentially different experiments [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] with the only one common feature, i.e., the limited number of interacting atoms during growth.…”
Section: Introductionmentioning
confidence: 89%
“…Nevertheless, the model did not allow us to explain the photostimulated luminescence of IHC samples submerged in bulk He II. Moreover, the model was not confirmed by structural studies of IHCs revealed nanoclusters as building units of the condensates [10][11][12].…”
Section: "Cold" and "Hot" Thermoluminescence Spectra From Ihcsmentioning
confidence: 94%
“…Such particles and systems have found many different applications: visualization of flows and quantum vortices in superfluid helium [2][3][4]; study of energy transfer phenomena in liquid helium [5]; development of new high-energy density materials [6][7][8]; investigation of tunneling reactions of hydrogen isotopes in impurity-helium condensates [9]; structural studies of rare gas, molecular deuterium and nitrogen nanoclusters [10][11][12]; study of cold neutron interaction with watergels [13,14]; synthesis of metallic nanowires in superfluid helium [15,16]. Laser ablation of metallic target in solid helium-4 allows to create so-called icebergs (helium crystals doped with metallic particles) remaining metastable below the melting curve [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…This method not only allowed exceptionally high concentrations of stabilized atoms (up to 10% atomic nitrogen in N-N 2 samples) [3] but also provided for a variety of significant experiments. Optical spectroscopy [4][5][6][7][8][9], ESR [10][11][12][13][14][15][16][17][18], x-ray diffraction [19][20][21][22][23] and ultrasound techniques [24][25][26][27] were used to characterize these samples and to determine why free radical stabilization was so effective. It was found that the samples of impurity helium condensates formed inside superfluid helium have a porous structure composed of nanoclusters of impurity species with characteristic size of order 5 nm [19].…”
Section: Introductionmentioning
confidence: 99%